Peningkatan Hasil Belajar Menggunakan Model Talking Stick pada Pembelajaran Tematik Terpadu di Sekolah Dasar - Zavitri, Novira; S, Farida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2022)
The purpose of this researchais to describe theaplanning, implementation and improvementclearning outcomes of students using a Talking Stick model in integrated thematic learning in grade IV Elementary School. This research uses PTK research with qualitative and quantitative approaches. This research was conducted at SDN 12 Bukit Cangang,  consists of 29 students. This study consisted of 2 cycles, namely cycle 1 consisted of 2 meetings, and cycle 2 consisted of 1 meeting. The results of this study indicate an increase in student learning outcomes, namely in the first cycle with an average value of 75 (B) and the second cycle with an average of 84. Based on this it can be said that the Talking Stick model can improve student learning outcomes.